Design and Implementation of Software Solutions for Satellite Ground Segment, with Application to the ESEO Mission - Bosco, Marco <1988> (Alma Mater Studiorum - Università di Bologna, 2016)
The work presented in this thesis focuses on the design and implementation of software solutions for the ground segment of satellite missions, with application to the ESEO mission. The ESEO project is currently in Phase D after successfully passing the preliminary and critical design reviews and the launch is foreseen in 2017. Starting from our experience with ALMASat-1 mission, we greatly improved the ground systems for a more complex mission like ESEO. One of the most important improvement is the introduction of a Software Defined Radio with a dedicated software application acting as a transceiver capable of communicating with the on-board transceiver at the registered frequencies and using the defined communication protocol and modulation scheme. It also displays and registers the acquired signal for post-processing tasks. The spacecraft monitoring and control system and the telemetry data visualisation and display tool have been designed keeping in mind the high number of subsystems and payloads and the possibility to re-use the same software for future missions with the minimum effort. The introduction of a connection to a database is essential considering the high number of spacecraft and mission data. This thesis also presents the software solutions designed and implemented for ground stations used by EUMETSAT to operate LEO and GEO weather satellites. The Ground Station Analysis and Reporting tool was developed to allow engineers checking through periodic reports the performance of two ground stations located in Svalbard. The Satellite Passes and Conflicts Engine supports now the schedule of Metop and NOAA satellite passes over Svalbard ground station and it can be used to compute passes and resolve conflicts of multiple satellites over multiple ground stations based on the propagation of the TLEs. Finally, a ground station monitoring and control simulator has been implemented and fully tested for the MTG programme.